Observed surface lysine acetylation of human carbonic anhydrase II expressed in Escherichia coli. (15th September 2015) - Mahon, Brian P.; Lomelino, Carrie L.; Salguero, Antonieta L.; Driscoll, Jenna M.; Pinard, Melissa A.; McKenna, Robert
Abstract Acetylation of surface lysine residues of proteins has been observed in Escherichia coli (E. coli), an organism that has been extensively utilized for recombinant protein expression. This post‐translational modification is shown to be important in various processes such as metabolism, stress‐response, transcription, and translation. As such, utilization of E. coli expression systems for protein production may yield non‐native acetylation events of surface lysine residues. Here we present the crystal structures of wild‐type and a variant of human carbonic anhydrase II (hCA II) that have been expressed in E. coli and exhibit surface lysine acetylation and we speculate on the effect this has on the conformational stability of each enzyme. Both structures were determined to 1.6 Å resolution and show clear electron density for lysine acetylation. The lysine acetylation does not distort the structure and the surface lysine acetylation events most likely do not interfere with the biological interpretation. However, there is a reduction in conformational stability in the hCA II variant compared to wild type (∼4°C decrease). This may be due to other lysine acetylation events that have occurred but are not visible in the crystal structure due to intrinsic disorder. Therefore, surface lysine acetylation events may affect overall protein stability and crystallization, and should be considered when using E. coli expression systems.